PENDIDIKAN NILAI SEBAGAI JAWABAN ATAS KRISIS MORAL GENERASI MUDA - Muchamad Rifki , Rafi Alfarizy Hadiyusron; Selvi Puspitasari , Sifa Salsabila (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The moral crisis of the young generation in Indonesia has become a serious problem triggered by globalization, the influence of digitalization, and weak character education. The purpose of this article is to see how Islamic value education functions as a comprehensive solution to overcome this crisis. This study uses a qualitative approach in literature research. Data were collected and analyzed from various related literature, such as books, journals, and scientific documents. Research shows that things like bullying, drug abuse, and free association that are detrimental to the young generation are caused by internal factors (lack of family supervision) and external factors (negative influence of technology). Islamic value education, which is based on the Qur'an and Sunnah, solves the problem through the development of noble morals, spiritual awareness, and social responsibility. To achieve this, three pillars must work together: family as the basis, school as a model for integrating values, and the environment as a supporter. It is proven that concrete programs such as spiritual guidance, case-based learning, and worship practices can build strong character. This study concludes that revitalizing Islamic value education is very important to create a generation that is morally good and academically intelligent.